2022
DOI: 10.4178/epih.e2022053
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on screening for colorectal, gastric, breast, and cervical cancer in Korea

Abstract: Objectives:The COVID-19 pandemic has affected the utilization of healthcare services, such as participation in cancer screening programs. We compared cancer screening participation rates for colorectal, gastric, breast, and cervical cancers among participants in the National Cancer Screening Program (NCSP) in 2019 and 2020 to address the potential distraction effect of COVID-19 on cancer screening.Methods: Data from the NCSP for four cancer types (stomach, colorectal, breast and cervical) in 2019 and 2020 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…This was when the aggregation of confirmed cases was low, with a daily average of 39.3 cases, and social distancing was converted to the degree of daily life 2 . A previous study reported that when comparing the monthly cancer screening rates in 2019 and 2020, the figure increased in June compared to March 2020 26 . Unlike cancer screening, it is extremely difficult to delay ED visits or endure sickness without urgent action due to the characteristics of CVD itself, well known as being time-sensitive.…”
Section: Discussionmentioning
confidence: 95%
“…This was when the aggregation of confirmed cases was low, with a daily average of 39.3 cases, and social distancing was converted to the degree of daily life 2 . A previous study reported that when comparing the monthly cancer screening rates in 2019 and 2020, the figure increased in June compared to March 2020 26 . Unlike cancer screening, it is extremely difficult to delay ED visits or endure sickness without urgent action due to the characteristics of CVD itself, well known as being time-sensitive.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, especially during the period of high-intensity social distancing, there was a significant decrease in the incidence of stomach, colorectal, liver cancer, and breast cancer. Considering that stomach, liver, colorectal, breast, cervical, and lung cancers, can be screened through the Korean National Cancer Screening Program [ 40 ], it can be attributed largely to the significant decrease in cancer screening rates during the COVID-19 pandemic [ 5 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the screening rate can also be influenced by external factors, such as the COVID-19 pandemic ( 32 , 33 ). In 2021, when COVID-19 was serious and several social distancing policies had been implemented, the opportunistic screening rate had increased to 18% from approximately 10% in previous years.…”
Section: Discussionmentioning
confidence: 99%